Evaluación de rendimiento del cuy a la canal bajo tres niveles de alimentación: 1 concentrado + raygrass, 2 alfalfa + afrecho + zanahoria, 3 concentrado + zanahoria, en la parroquia Cutuglagua, cantón Mejía, provincia de Pichincha - Montalvo Vela, Mercedes (2011)
The chapter one in this investigation contain the literature review shows the important aspects when starting a proper breeding of guinea pigs, is important to know deeply their morphological, physiological, reproductive, food habits and others, and thus the producer knows the right way to raise these animals, so that this activity will improve the production for marketing, either within or outside the sector. In the section from chapter two addresses issues related to materials and methods which include, the experiment place characteristics, types of studies conducted in this research, experimental design, test management, identifying variables, among other aspects that involved in carrying out this research....